2009
DOI: 10.4047/jap.2009.1.3.113
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low temperature aging on the mechanical property & phase stability of Y-TZP ceramics

Abstract: STATEMENT OF PROBLEMRecently Yttrium-stabilized tetragonal zirconia polycrystal (Y-TZP) has been introduced due to superior flexural strength and fracture toughness compared to other dental ceramic systems. Although zirconia has outstanding mechanical properties, the phenomenon of decrease in the life-time of zirconia resulted from degradation in flexural strength after low temperature aging has been reported.PURPOSEThe objective of this study was to investigate degradation of flexural strength of Y-TZP cerami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 20 publications
6
109
3
1
Order By: Relevance
“…However, increased strength after an accelerated aging treatment has to be considered specific for the evaluated prototype implant of the present investigation and cannot be taken as general rule for Y-TZP [16]. At some point when the degradation process penetrates deeper into the material, the contribution from the aging may instead cause the strength of the same sample to be decreased [8]. Moreover, mechanical treatment also resulted in increased strength.…”
Section: 6mentioning
confidence: 95%
See 1 more Smart Citation
“…However, increased strength after an accelerated aging treatment has to be considered specific for the evaluated prototype implant of the present investigation and cannot be taken as general rule for Y-TZP [16]. At some point when the degradation process penetrates deeper into the material, the contribution from the aging may instead cause the strength of the same sample to be decreased [8]. Moreover, mechanical treatment also resulted in increased strength.…”
Section: 6mentioning
confidence: 95%
“…Once started, phase transformation continuously progresses from the surface into the volume in a layer-by-layer manner, following a linear time law [7]. Aging can result in intergranular micro-cracking, surface-roughening and, up from a certain level, in reduced strength [8]. Finally, PTT and LTD are based upon the same phenomenon and using Y-TZP for the fabrication of biomedical implants, one might not exploit the advantage of the former without being exposed to the risk of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia FDPs are feasible for molar region, due to their high flexural strength and fracture toughness [12][13][14][15]. Limited number of clinical studies reported seldom zirconia framework fractures but more often chipping of the veneering ceramic [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the tetragonal phase at room temperature, zirconia-based ceramics must be stabilized by adding oxides. Yttria is a popular stabilizing additive, giving Y-TZP 12,13,16) . This new ceramic is useful as a prosthetic frame material because of its high fracture toughness and its precision fabrication with dental CAD/CAM systems.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the 21st century, zirconium dioxide (ZrO 2: zirconia), a new and tough ceramic material, has been receiving increasing attention in dentistry [12][13][14][15][16] . Initially, its use was restricted to metalfree fixed partial anterior dentures, but its use is being extended to a variety of applications, such as fixed partial posterior dentures, orthodontic brackets 19) and dental implant abutment or fixture 20,21) , as well as simple dental restoration or prostheses 17,18) .…”
Section: Introductionmentioning
confidence: 99%